New species and new song record of the genus Dociostaurus Fieber, 1853 (Orthoptera, Acrididae, Gomphocerinae) from Southern Anatolia, Turkey - Şi̇ri̇n, Deni̇z; Mol, Abbas (Zootaxa, 2013)
The new species Dociostaurus (Kazakia) icconium Şirin & Mol sp. n. (Orthoptera, Acrididae, Gomphocerinae) is de-scribed on the basis of morphology and male calling song. The congeneric partner of new species is Dociostaurus (Stau-ronotulus) cappadocicus (Azam, 1913) whose song description is done for the first time in this study. The species Dociostaurus (Kazakia) brevicollis (Eversmann, 1848) is assumed to be the closest relative of Dociostaurus (Kazakia) icconium sp. n.. The relationships between the new species and the relatives/congeneric partners were evaluated by using both song and morphological characters, for which illustrations were provided. Finally, a brief remark on the distribution pattern of the species was given.